1932
DOI: 10.1021/ja01344a044
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES OF CONJUGATED SYSTEMS. XI. THE OXIDATION OF CIS-PHENYLBUTADIENE BY MEANS OF PERBENZOIC ACID1

Abstract: Perbenzoic and peracetic acids have been used for some time to determine the degree of unsaturation and the rate of oxidation of olefinic compounds.2 Of particular interest in our investigations is the work of Bóeseken and Blumberger on the three isomeric phenylbutenes, 1,2-C6H6-CH=CH-CH2-CH3; A2'3-C6H6-CH2-CH=CH-CH3; 3,4-C6H5-CH2-CH2-CH=CH2; and also on cinnamic acid and its methyl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1947
1947
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although considerable evidence has been collected that the reaction proceeds as shown in the equation, some workers (376,511) have suggested that the peracid adds directly to the double bond, followed by splitting out of benzoic acid. This erroneous idea has found its way into a standard reference work on organic chemistry (2).…”
Section: C=c-+ Ch»c03hmentioning
confidence: 99%
“…Although considerable evidence has been collected that the reaction proceeds as shown in the equation, some workers (376,511) have suggested that the peracid adds directly to the double bond, followed by splitting out of benzoic acid. This erroneous idea has found its way into a standard reference work on organic chemistry (2).…”
Section: C=c-+ Ch»c03hmentioning
confidence: 99%
“…(10) Filachione, E. M., 'Lengel, J. H., and Fisher, C. H., Ibid., 37, 388 (1945). (11) Filachione, E. M., Lengel, J. H., and Fisher, C. H., J. Am.…”
Section: Literature Citedmentioning
confidence: 99%
“…The first study of perbenzoic acid addition to double bonds was made by Prileschajew (IS), but the usefulness of the reaction has been confined to the preparation of hydroxy benzoates (11,12) and epoxides (2). Other peracids-peracetic (16), percamphoric (10), and perphthalic (3)-have been used as addition reagents in syntheses.…”
Section: Literature Citedmentioning
confidence: 99%